Left Ventricular Hypertrophy and Remodeling and Risk of Cognitive Impairment and Dementia: MESA (Multi-Ethnic Study of Atherosclerosis). Issue 3 (March 2018) - Moazzami, Kasra; Ostovaneh, Mohammad Reza; Ambale Venkatesh, Bharath; Habibi, Mohammadali; Yoneyama, Kihei; Wu, Colin; Liu, Kiang; Pimenta, Isabel; Fitzpatrick, Annette; Shea, Steven; McClelland, Robyn L.; Heckbert, Susan; et al.
Abstract : Limited information exists on the longitudinal association between the left ventricular (LV) structure and function and future cognitive impairment and dementia in a large population without clinically recognized cardiovascular disease at baseline. The aim of the present study was to investigate the association between cardiac structure and function and risk of dementia and cognitive impairment in the MESA (Multi-Ethnic Study of Atherosclerosis) cohort. Measures of LV structure and function were determined using magnetic resonance imaging at baseline in 4999 participants free of clinically diagnosed cardiovascular disease and dementia. Probable incident clinical dementia was ascertained from hospitalization discharge records. Cognitive function was evaluated using tests addressing global cognitive function, processing speed, and memory. Associations of measures of LV structure and function with the incidence of clinically diagnosed dementia and cognitive performance were evaluated using Cox proportional hazard regression models adjusted for demographics, cardiovascular risk factors, and cardiovascular events. During a median follow-up of 12 years, 130 probable incident dementia cases were documented. Higher LV mass index (hazard ratio, 1.01; 95% confidence interval, 1.00–1.02) and LV mass-to-volume ratio (hazard ratio, 2.37; 95% confidence interval, 1.25–4.43) were independently associated with incident dementia and impaired cognitive function. Measures of LV function were not associated with risk of dementia or cognitive impairment. In conclusion, in a multiethnic cohort of participants without clinically detected cardiovascular disease and dementia at baseline, LV hypertrophy and concentric remodeling were independently associated with incident dementia and cognitive impairment. Abstract : Supplemental Digital Content is available in the text.